Clinical Outcome of Cooled Radiofrequency Ablation in Chronic Knee Pain Osteoarthritis: An Initial Experience from Nepal - Rayamajhi, Anuj Jung; Hamal, Pawan Kumar; Yadav, Rupesh Kumar; Pokhrel, Nabin; Paudel, Prashanta; Paudel, Subash Chandra; Dhungel, Bidur Kumar (Journal of Nepal Health Research Council, 2021)
Background: Cooled Radiofrequency ablation is a newer technique for management of chronic knee pain in osteoarthritis. The aim of the study is to evaluate the clinical outcomes in patients with chronic osteoarthritis in terms of pain scores for first six months of cooled radiofrequency ablation using ultrasound guidance. Methods: A cross-sectional study with retrospective review of database was evaluated to analyze the change in the Numerical Rating Scale from baseline scores at 1 day, 1 month and 6 months after the Cooled Radiofrequency ablation of genicular nerves around knee in patients with chronic knee osteoarthritis. Results: Median age was 71 years [ 61-73 years (IQR: 25-75)] with more female preponderance. Numerical Rating Scale (Mean ± S.D.) was significantly less at 1 day (1.87 ± 1.22), 1 month (3.03 ± 0.99) and 6 months (3.37 ± 1.098) from baseline values (6.77 ± 1.00). No soreness and numbness were noted.Conclusions: Cooled Radiofrequency using Ultrasound guidance for management of knee pain in chronic osteoarthritis is promising and reduces Numerical Rating Score significantly from baseline at 1 month and 6 months respectively.Keywords: Cooled radiofrequency ablation; genicular nerve; numeric rating scale